Case study: Nutrition and training periodization in three elite marathon runners - Stellingwerff, T. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
Laboratory-based studies demonstrate that fueling (carbohydrate; CHO) and fluid strategies can enhance training adaptations and race-day performance in endurance athletes. Thus, the aim of this case study was to characterize several periodized training and nutrition approaches leading to individualized race-day fluid and fueling plans for 3 elite male marathoners. The athletes kept detailed training logs on training volume, pace, and subjective ratings of perceived exertion (RPE) for each training session over 16 wk before race day. Training impulse/load calculations (TRIMP; min × RPE = load [arbitrary units; AU]) and 2 central nutritional techniques were implemented: periodic low-CHO-availability training and individualized CHO- and fluidintake assessments. Athletes averaged ~13 training sessions per week for a total average training volume of 182 km/wk and peak volume of 231 km/wk. Weekly TRIMP peaked at 4,437 AU (Wk 9), with a low of 1,887 AU (Wk 16) and an average of 3,082 ± 646 AU. Of the 606 total training sessions, ~74%, 11%, and 15% were completed at an intensity in Zone 1 (very easy to somewhat hard), Zone 2 (at lactate threshold) and Zone 3 (very hard to maximal), respectively. There were 2.5 ± 2.3 low-CHO-availability training bouts per week. On race day athletes consumed 61 ± 15 g CHO in 604 ± 156 ml/hr (10.1% ± 0.3% CHO solution) in the following format: ~15 g CHO in ~150 ml every ~15 min of racing. Their resultant marathon times were 2:11:23, 2:12:39 (both personal bests), and 2:16:17 (a marathon debut). Taken together, these periodized training and nutrition approaches were successfully applied to elite marathoners in training and competition.